Wrist Arthroscopy under Portal Site Local Anesthesia (PSLA) without Tourniquet - Ong, Michael T. Y.; Ho, P. C.; Wong, Clara W. Y.; Cheng, Sally H. S.; Tse, Wing- Lim (Journal of Wrist Surgery, 2012)
Purpose wrist arthroscopy is typically performed under general or regional anesthesia with the aid of a tourniquet to maintain a bloodless field. We have been using portal site local anesthesia (PSLA) for wrist arthroscopy without a tourniquet since 1998. The aim of the study was to assess the efficacy, safety, and complications of PSLA and whether this can be recommended for routine wrist arthroscopy.Method We conducted a retrospective study, identifying 111 consecutive cases of wrist arthroscopies performed from January 2007 to December 2009. All cases were performed under PSLA. The effectiveness of PSLA was assessed by analyzing whether the procedure required adjuvant forms of anesthesia. The subjective effectiveness was assessed via phone questionnaires.Results Sixty-eight male and 43 female patients were identified. The average age was 43.2 (range 16–77). The indications included chronic wrist pain of unknown origin (30), posttraumatic arthritis (27), rheumatoid arthritis (5), ganglion (30), triangular fibrocartilage complex (TFCC) injury (14), infectious (1), and carpal instability (4). The average duration of the procedures was 73 minutes (range 20–255 minutes). Therapeutic procedures were performed in all 111 cases in addition to a routine diagnostic assessment. These included arthroscopic debridement (82) synovectomy (6), ganglionectomy (30), TFCC repair (3), TFCC debridement (11), radial styloidectomy (2), wafer procedure (4), thermal shrinkage (2), distal scaphoidectomy (1), and synovial biopsy (4). All procedures could be completed uneventfully. Most patients tolerated the procedure well throughout the operation, and the satisfaction level was high. No complication was encountered.Discussions We concluded that PSLA technique is a feasible mode of anesthesia in selected patients. Level of evidence: Level IV
Keywords: wrist; arthroscopy; portal site; local anesthesia